A173 RECOGNIZING RARE PRESENTATIONS OF POLYPOSIS SYNDROMES AND THEIR ASSOCIATED MALIGNANCIES IN PEDIATRIC PATIENTS. (26th February 2020) - Reitzel, N E; Sherlock, M; Zachos, M; Arredondo, J; Ratcliffe, E
Abstract: Background: There is a range of polyposis syndromes and presentations in pediatrics. There are also associated extra-colonic malignancies of which to be cognizant when orchestrating the initial work-up of the various polyposis syndromes. Aims: To use case review to highlight the importance of recognizing the breadth of presentations of polyposis syndromes in pediatrics. Methods: Two recent pediatric presentations of polyposis with extra-intestinal manifestations were identified, chart review completed, and compared with newly published ESPGHAN guidelines. Results: Two patients with intestinal polyposis are presented, in which extra-colonic malignancies and genetic mutations were identified. The first patient presented at age 16 with a history of fatigue and abdominal pain, and was found to have pancytopenia and splenomegaly. Initial work up included a bone marrow biopsy that was normal. The patient then underwent upper and lower endoscopic evaluation for increasing abdominal pain and persistent anemia and was found to have polymorphic polyps in the duodenum, sigmoid and rectum. On pathology, polyps were mostly inflammatory, but one was found to be hamartomatous. Additional screening revealed a thyroid nodule, found to be follicular carcinoma, requiring hemithyroidectomy. The patient was confirmed to have a PTEN mutation and was diagnosed with Cowden syndrome; following this diagnosis proceeded with a prophylactic bilateral mastectomy. The second patient was referred at age 15 with a strong family history of APC-associated FAP. At the time of consultation she was asymptomatic and she remained so throughout her work-up. Screening endoscopy revealed 70–90 recto-sigmoid adenomatous polyps as well as scattered gastric and duodenal polyps. Her initial work-up also uncovered an early papillary thyroid carcinoma. Her treatment included a total thyroidectomy and total proctocolectomy with J-pouch and ileoanal anastomosis. Follow-up endoscopy continues for surveillance of numerous gastric adenomas which to this point have not progressed to high-grade dysplasia or malignancy. Conclusions: These 2 cases highlight the importance of recognizing that neoplastic conditions typically diagnosed in adulthood can also present in the pediatric age group. Ideally, further guidelines in pediatrics would be beneficial to ensure a consistent approach to investigating polyposis and associated malignancies. Pertaining to our specific patients, each had identification of a thyroid malignancy before the recommended screening age of 18 as per the currently accepted guideline, and neither were symptomatic. More cases are needed to establish if this earlier recognition of disease is meaningful in postulating potential mortality associated with a later diagnosis. Funding Agencies: None